2014
DOI: 10.1111/apt.12678
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: meat consumption and the risk of hepatocellular carcinoma

Abstract: SUMMARY BackgroundThe association between meat consumption and the risk of hepatocellular carcinoma (HCC) is still inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 50 publications
2
36
1
Order By: Relevance
“…Interestingly, a recent meta-analysis of seven cohort and ten case-control studies indicated a potential protective association between BCAA and HCC risk (79) . However, to date, there has been no epidemiological research to directly investigate the putative association between dietary BCAA intake and liver cancer risk to our knowledge.…”
Section: Dietary Proteins/amino Acidsmentioning
confidence: 99%
“…Interestingly, a recent meta-analysis of seven cohort and ten case-control studies indicated a potential protective association between BCAA and HCC risk (79) . However, to date, there has been no epidemiological research to directly investigate the putative association between dietary BCAA intake and liver cancer risk to our knowledge.…”
Section: Dietary Proteins/amino Acidsmentioning
confidence: 99%
“…The summary of all cancer studies by the World Cancer Research Fund and American Institute for Cancer Research in 2007 concluded that the available scientific evidence was convincing that the consumption of processed and unprocessed red meat was associated with the increased risk of colorectal cancer [57]. Summary results from the most recent meta-analyses (2009-2015) based on prospective cohort studies of 11 cancer types [58][59][60][61][62][63][64][65][66][67][68] are presented in Table 2 and illustrated in Fig. 4.…”
Section: Cancermentioning
confidence: 99%
“…It is of great significance to find novel strategies to prevent HCC, dietary and nutritional factors have presented an attractive prospect. In addition to vegetables, recent epidemiological studies have suggested that higher consumption of coffee, fish and white meat is helpful to prevent HCC 47,48 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%